THE THEME OF THE EAST IN ENGLISH LITERATURE - Toshpulatov Bekhzod Bekmurod o’g’li (Journal of new century innovations, 2023)
Abstract: Of all the forms of literature drama is, perhaps, the most faithful reflection of contemporary life. The ideals and aspirations, the prejudices and fears, the social, cultural and ethical values of a society find eloquent expression in its drama. The Elizabethan drama, in particular, being the product of a buoyant and self-confident age, is uninhibited in expression. References to the East abound in almost all dramatists of the age. These references, taken together, tell a story—the story of how the West felt toward the East. The present study aims at dealing with characters from the East and the allusions to the East in the English dramas prose. This article describes some basic features of East in English literature.